Pembrolizumab-Induced Hypertrophic Lichen Planus in Patient with Hepatocellular Carcinoma - Chancheewa, Bussabong; Pongprutthipan, Marisa (Thai Journal of Dermatology, 2023)
Pembrolizumab, an anti-programmed cell death-1 (PD-1) antibody, is a highly effective targeted therapy for many cancers, including hepatocellular carcinoma (HCC). Besides the excellent efficacy, one of the major reported downsides of this drug are the cutaneous adverse events, which can be presented in various forms. In this case report, we demonstrate a case of hypertrophic lichen planus (LP) after receiving pembrolizumab for 1 month. The initial diagnosis was made using dermoscopy and the diagnosis was confirmed by skin biopsy. Our patient was treated with intralesional corticosteroid which provided an excellent outcome. After the treatment, this patient can resume HCC treatment, using pembrolizumab. Hypertrophic LP is an unusual AE of pembrolizumab, the correct diagnosis and early treatment are critical for drug continuation.